Dual cultivation with endomycorrhizal host plants makes effective endomycorrhizal symbiosis in Intsia bijuga (Colebr.) Kuntze in greenhouse experiments. - Nirina Rakotoarimanga; Abel Andriantsimahavandy; Robin Duponnois (Asosiasi Mikoriza Indonesia, 2023)
The aim of this work was to highlight the establishment of endomycorrhizal symbiosis in Intsia bijuga under certain conditions related to the presence of endomycorrhizal plants and show the effectiveness of symbiosis. The experiments were conducted at greenhouse. Single and dual cultivation of Intsia bijuga with each of the three different species of endomycorrhizal host plants (Zea mays, Crotalaria juncea and Dalbergia trichocarpa) on sterilized poor soil and forest soils (sterilized and unsterilized) were performed. On sterilized poor soil, the culture was inoculated by inoculums of endomycorrhizal fungi Glomus intraradices (syn. Rhizophagus irregularis). The effectiveness of the endomycorrhizal establishment was evaluated by the colonization of the roots by endomycorrhizae, the rate of Nitrogen and Phosphorus accumulated in leaves and plant mycorhizal dependency. Dual cultivation of Intsia bijuga with each of the three endomycorhizal host plants allowed endomycorhizal establishment in its roots and Intsia bijuga development was significantly improved by endomycorrhizal establishment. The biomass and the rates of N and P were significantly high in endomycorrhizal plants. Mycorrhizal dependency of Intsia bijuga in dual cultivation either with Crotalaria juncea or with Dalbergia trichocarpa (legumes) was lower than those with Zea mays. Endomycorrhizal symbiosis was effective in Intsia bijuga cultivated with endomycorrhizal host plants.